UWB Directive Triangular Patch Antenna - A. C. Lepage; X. Begaud; G. Le Ray; A. Sharaiha (International Journal of Antennas and Propagation)
Compact directive UWB antennas are presented in this paper. We propose an optimization of the F-probe fed triangular patch antenna. The new design achieves an impedance bandwidth of 69% (3–6.15 GHz) and presents good radiation characteristics over the whole impedance bandwidth. The average gain is 6.1 dB. A time-domain study has been performed to characterize the antenna behavior in case a UWB pulse is used. Finally, we propose an alternative solution to facilitate the manufacturing process using metallized foam technology. It also improves the robustness of the antenna as well as reducing its cost.